On Boundary Value Problems for φ-Laplacian on the Semi-Infinite Interval. Issue 1 (2nd January 2017) - Lepin, Arnold; Lepin, Leonid; Vasilyev, Nickolay
Abstract: The Dirichlet problem and the problem with functional boundary condition for φ -Laplacian on the semi-infinite interval are studied as well as solutions between the lower and upper functions.